2005
DOI: 10.22146/gamaijb.5574
|View full text |Cite
|
Sign up to set email alerts
|

A Test of the Relationships among Perceptions of Justice, Job Satisfaction, Affective Commitment and Organizational Citizenship Behavior

Abstract: This study examines factors influencing organizational citizenship behavior in an organization. These factors include procedural justice, distributive justice, job satisfaction and commitment. Although previous studies have investigated commitment as antecedent of OCB, most of them did not specifically explain the type of commitment hypothesized. In terms of commitment, this study utilizes the specific type of commitment, i.e. affective commitment. The theoretical model proposes both distributive justice and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
1
13

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 33 publications
6
30
1
13
Order By: Relevance
“…The correlation that exists in this study between fairness perception and job satisfaction corresponds with (Rifai, 2005;Paik et al, 2007;Deconinck and Bachmann, 2007) who reported that significant positive relationships exist between procedural and distributive justices as independent variables and job satisfaction as a dependent variable. The result also corroborates Khalifa and Truong (2010)'s findings that perceptions of equity among academic employees of Egyptian private universities were positively related to their job satisfaction, with perception of recognition fairness being the best predictor of job satisfaction.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The correlation that exists in this study between fairness perception and job satisfaction corresponds with (Rifai, 2005;Paik et al, 2007;Deconinck and Bachmann, 2007) who reported that significant positive relationships exist between procedural and distributive justices as independent variables and job satisfaction as a dependent variable. The result also corroborates Khalifa and Truong (2010)'s findings that perceptions of equity among academic employees of Egyptian private universities were positively related to their job satisfaction, with perception of recognition fairness being the best predictor of job satisfaction.…”
Section: Discussionsupporting
confidence: 80%
“…The relationship between perceptions of fairness and job satisfaction has been investigated by several researchers (McIntyre et al, 2002;Rifai, 2005;Paik et al, 2007;Lambert et al, 2007;Deconinck and Bachmann, 2007;Khalifa and Truong, 2010). For instance, the findings of Rifai's (2005) study on the factors that influence organizational citizenship behaviours reveal that significant positive relationships exist between procedural justice and distributive justice as independent variables and job satisfaction as dependent variable.…”
Section: Relationship Amongst Perceptions Of Fairness Job Satisfactimentioning
confidence: 99%
See 1 more Smart Citation
“…), which will involve internal as well as external customers in determining processes related to the decisions on benefits, the provision of adequate information on how rewards and punishments are determined, and the excellent and timely management of complaints by society. Furthermore, managing the company non-financial performance may serve to minimize the customers' reactions to perceived unequal outcomes (e.g., a pay raise policy based on the merit pay system) (Rifai 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Araştırmacılar arasında örgütsel adaletin kaç boyutta inceleneceği konusunda farklı görüşler bulunmaktadır. Örgütsel adaletin genel olarak dağıtım adaleti ve işlemsel adalet olmak üzere iki önemli boyutta incelendiği görülmektedir (Mc Farlin ve Sweeney, 1992;Love ve Vodanovic, 1995;LemonsveJones, 2001;Rifai, 2005). Diğer yazarlar ise örgütsel adaleti dağıtımsal adalet, prosedürel (işlem) adalet ve etkileşimsel adalet olmak üzere üç boyutta incelemektedir (Öğüt vd., 2009;Foley, Kidder ve Powell, 2002;Folger, 1987;Greenberg, 1990).…”
Section: Li̇teratür Taramasiunclassified